The RE-STEAM Approach in Learning for Enhancing Students Moral Character and Communication Skills at MTs Negeri 2 Wonosobo - Dwi Kartika Sari; Z Sukawi; Robingun Suyud El Syam; Firdaus Firdaus; Cindy Agustin (Journal of Education Technology and Inovation, 2025)
Conventional approaches in Aqidah Akhlak learning tend to limit the contextualization of Islamic teachings in students’ real-life experiences, resulting in weak internalization of moral values and communication skills. The RE-STEAM (Religion, Science, Technology, Engineering, Art, and Mathematics) approach is considered a potential solution to this issue. This study aims to analyze the implementation of RE-STEAM-based Aqidah Akhlak learning in strengthening students’ moral character and communication skills at MTs Negeri 2 Wonosobo. This research employed a descriptive qualitative field study. Informants consisted of the madrasa principal, vice principal for curriculum affairs, and three Islamic education teachers, while the research subjects included one Aqidah Akhlak teacher and Grade VIII students. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and verification techniques. Data validity was ensured through source, technique, and time triangulation. The findings reveal that the RE-STEAM approach was implemented through integrated in-class and out-of-class activities combining religious values with science, technology, engineering, art, and mathematics. The approach fostered transformative learning experiences reflected in improved student behavior, self-reflection practices, and commitment to moral improvement. Furthermore, learning became more interactive and communicative, as evidenced by active discussions, presentations, and the creation of digital flowcharts, infographics, and posters integrating Islamic messages with technology. This study contributes empirical evidence on integrated RE-STEAM learning to strengthen moral values and communication skills in madrasa education.